Implementation Of The Legislative Function Of The Regional People's Representative Council (DPRD) Of Madison District In The Preparation Of Local Regulations - Sarjiyati; Sigit Sapto Nugroho; Subadi; Taufiq Yuli Purnama; Endang Sri Mulyani (Universitas Merdeka Madiun, 2024)
Abstract Introduction to the Problem : The factors that hinder the implementation of the legislative function of the Madiun Regency DPRD in the formation of Madiun Regency Regional Regulations. Purpose /Study Objectives : Describe the implementation of the legislative function of the Madiun Regency DPRD in the formation of Madiun Regency Regional Regulations . Design/Methodology/Approach : The research method used is empirical juridical. Data was collected by literature study, interviews, and documentation. Findings : The results showed that the implementation of the legislative function of the Madiun Regency DPRD in the formation of Madiun Regency Regional Regulations is in line with Law Number 12 of 2011 concerning the Formation of Legislation, Factors that become obstacles in the implementation of the legislative function of the Madiun Regency DPRD in the formation of Madiun Regency Regional Regulations come from internal and external factors. Internal factors include educational factors or human resources, data or information availability factors, experience factors owned by DPRD members, as well as conflicts of interest between special committee members and the proposed ideas of each special committee member are often different. Meanwhile, external factors include the interests of stakeholders or stakeholders that conflict with the local regulation and the absence of stakeholders at the discussion meeting of the draft regulation. Paper Type : Research Article